Identifying and quantifying natural CO2 sequestration processes over geological timescales: The Jackson Dome CO2 Deposit, USA - Zhou, Z; Ballentine, C; Schoell, M; Stevens, S (2012)
CO 2 sources, sinks and migration mechanisms in natural CO 2 gas fields provide critical analogues for developing the safe application of anthropogenic CO 2 sequestration technologies. Here we use noble gas and carbon isotopes, together with other gases, to identify and quantify the origin, transport and trapping mechanisms of CO 2 in the Late Cretaceous Jackson Dome CO 2 gas deposit (98.75% to 99.38% CO 2). Located in central Mississippi, USA, and producing from >5000m, it is one of the deepest commercial CO 2 gas fields in the world. 10 gas samples from producing wells were determined for their noble gas, chemical and stable carbon isotope composition. 3He/ 4He ratios range between 4.27R a and 5.01R a (where R a is the atmospheric value of 1.4×10 -6), indicating a strong mantle signature. Similar to CO 2 deposits worldwide, CO 2/ 3He decreases with increasing groundwater-derived 20Ne (and 4He). We model several different processes that could account for the Jackson Dome data, and conclude that, similar to other CO 2 dominated deposits, a Groundwater Gas Stripping and Re-dissolution (GGS-R) process best accounts for observed 20Ne/ 36Ar, 84Kr/ 36Ar, CO 2/ 3He, δ 13C(CO 2), 4He, 20Ne and 36Ar. In this context, crustal and magmatic CO 2 components contribute 57% and 43%, respectively. Changes in CO 2/ 3He across the field show that groundwater contact is responsible for up to 75% loss of original emplaced CO 2. δ 13C(CO 2) variance limits the degree of precipitation to be less than 27%, with the remaining CO 2 loss being accounted for by dissolution only. A higher degree of dissolution gas loss and evidence for water contact at the reservoir crest compared to the reservoir flanks is used to argue that CO 2 in this system has not undergone subsequent loss to either dissolution or precipitation since shortly after reservoir filling at over 60Ma. © 2012 Elsevier Ltd.